2012
DOI: 10.1111/aas.12024
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheters in infants and children – indications, techniques, complications and clinical recommendations

Abstract: Venous access required both for blood sampling and for the delivery of medicines and nutrition is an integral element in the care of sick infants and children. Peripherally inserted central catheters (PICCs) have been shown to be a valuable alternative to traditional central venous devices in adults and neonates. However, the evidence may not extrapolate directly to older paediatric patients. In this study, we therefore review the indications, methods of insertion and complications of PICC lines for children b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(145 citation statements)
references
References 62 publications
0
134
0
11
Order By: Relevance
“…These catheters have a diameter between 1.9 and 3Fr for neonates, are single or double-lumen, made of polyurethane or silicone. (1) The PICC is indicated for intermittent or continuous infusion of intravenous solutions, for short or long term, with vesicant and irritant characteristics, pH <5 or> 9, and solutions with osmolality higher than 600mOsm/L. (2) However, this use is not without risk.…”
Section: Introductionmentioning
confidence: 99%
“…These catheters have a diameter between 1.9 and 3Fr for neonates, are single or double-lumen, made of polyurethane or silicone. (1) The PICC is indicated for intermittent or continuous infusion of intravenous solutions, for short or long term, with vesicant and irritant characteristics, pH <5 or> 9, and solutions with osmolality higher than 600mOsm/L. (2) However, this use is not without risk.…”
Section: Introductionmentioning
confidence: 99%
“…Essas características específicas do CCIP devem ser orientadas para o paciente e seu familiar, verificando a sua compreensão e a sua concordância antes do procedimento (1,3,12,15) . A fala a seguir corrobora os achados na literatura.…”
Section: Metodologiaunclassified
“…A utilização do CCIP vem sendo difundida no Brasil a partir dos anos 1990, em unidades neonatais, pediátricas, oncológicas e mais recentemente nos cuidados domiciliares (1,2) . A sua expansão está relacionada: à redução do índice de infecção em comparação com outros cateteres centrais; à redução do uso de anestésicos; à realização do procedimento no leito; e à diminuição de intercorrências durante a punção em região central -pneumotórax, hemotórax, lesão do plexo braquial e embolia gasosa (1)(2)(3) . A experiência com o CCIP no Hospital de Clínicas de Porto Alegre (HCPA) iniciou em 1999, mas, somente em 2008, quando houve a introdução do CCIP valvulado (impede refluxo e não necessita de infusão contínua), que o cateter obteve ampla utilização no hospital.…”
Section: Introductionunclassified
“…The most common complications that lead to the non-elective removal of the PICC in neonates and children include the mechanics, such as obstruction, accidental pull, rupture and leakage of catheter, as well as infectious complications, phlebitis and thrombosis (8) . A cohort study conducted at a NICU in São Paulo analyzed 270 PICCs and reported an incidence of non-elective removal in 35.4% of cases, and an incidence rate of 34.8 / 1000 catheters--day, for the 1.9 Fr silicone catheter and the most frequent complications were external rupturing and obstruction (9) .…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study conducted at a NICU in São Paulo analyzed 270 PICCs and reported an incidence of non-elective removal in 35.4% of cases, and an incidence rate of 34.8 / 1000 catheters--day, for the 1.9 Fr silicone catheter and the most frequent complications were external rupturing and obstruction (9) . The obstruction may be thrombotic or non-thrombotic; non--thrombotic blockages are caused by the precipitation of incompatible drugs and multiple infusions through the catheter lumen, and the thrombotic blockage by clots (8) .…”
Section: Introductionmentioning
confidence: 99%